ON THE TIME FREQUENCY DEPENDENCIES OF THE SECULAR DECREASE RATE OF CASSIOPEIA A RADIO EMISSION - Vinyajkin, E. N. (Одеські астрономічні публікації, 2017)
Flux densities of young supernova remnant Cassiopeia A relative to those for radiogalaxy Cygnus A were measured in 1977-1992 at the frequencies of 290 and 927 MHz. These measurements were made with the same 10 m radiotelescopes at the Staraya Pustyn Radioastronomical Observatory (NIRFI). Decline of flux densities with time is not a steady one. There are deflections up to ±3% (±3 – 7σ) from the fitted power or linear time dependencies. The mean values of the rate of the flux densities decrease was determined to be (0.88± 0.11)% per year at the frequency of 290 MHz and (0.71 ± 0.09)% per year at the frequency of 927 MHz. The latter value is somewhat smaller than the value of (0.95 ± 0.04)% per year for 927 MHz flux density decrease rate over 1962-1977 (Vinyajkin E.N., Razin V.A.: 1979, Austral. J. of Phys., 32, 93). The mean values of an annual decrease in 290 and 927 MHz Cassiopeia A flux densities over 1977-1992 do not contradict qualitatively with the frequency dependence of the secular decrease rate obtained by Vinyajkin E.N., Razin V.A., Khrulev V.V.: 1980. Pisma Astron. Zh., 6, 620.